A Water Balance Model Based on Budyko Framework and Its Calibration through Particle Swarm Optimization Algorithm - Umut Okkan; Umut Kırdemir (Doğal Afetler ve Çevre Dergisi)
In the study presented, to define monthly rainfall-runoff relation, a water budget model based on Budyko approach was used. Proposed five-parameter model requires only monthly mean precipitation and potential evapotranspiration data as input. The study region covers the Nif Creek located at the Gediz Basin. Model was calibrated with particle swarm optimization (PSO) algorithm. To validate the performance of model calibrated via PSO, statistical measures were assessed. The results derived from the study show that water budget model is successful in modeling of monthly runoff series.